A charger shell molding process

Through the combination of polyphenylene ether resin, polycarbonate and ASA resin, combined with silane coupling agent and modified filler, the problems of poor processing fluidity and general impact resistance of polyphenylene ether resin materials are solved, and the charger shell material is realized High liquidity and comprehensive performance improvement.

CN118459969BActive Publication Date: 2025-02-11DONGGUAN GERUI ELECTRONIC TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410618354.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-17
Publication Date
2025-02-11
Estimated Expiration
2044-05-17

AI Technical Summary

Technical Problem

As a material for car charger shell, polyphenylene ether resin has problems such as poor processing fluidity, tendency to crack and general impact resistance, which affects its applicability.

Method used

The fluidity and impact resistance of the material are improved by combining polyphenylene ether resin, polycarbonate and ASA resin, combined with the use of silane coupling agent and modified filler.

Benefits of technology

Improves the flowability and processing properties of the charger housing material, enhances tensile strength and bending strength, while improving impact resistance and thermal deformation temperature.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_9
    Figure SMS_9
Patent Text Reader

Abstract

The present invention provides a charger shell molding process, comprising the following steps: (1) weighing the following raw materials in parts by mass: 50-60 parts of polyphenylene ether resin, 14-19 parts of polycarbonate, 10-17 parts of ASA resin, 1.5-2.5 parts of silane coupling agent, 4-6 parts of modified filler, 0.5-1 parts of lubricant, 0.3-0.8 parts of antioxidant, 1-3 parts of toughening agent, 1-2 parts of thermal stabilizer and 0.3-0.7 parts of anti-dripping agent; (2) mixing polyphenylene ether resin, polycarbonate, ASA resin, modified filler and silane coupling agent to obtain a premix; (3) adding the remaining components to the premix to obtain a final mixture; (4) melt blending the final mixture through a twin-screw extruder to obtain pellets; (5) hot-melt extruding the pellets to obtain a charger shell. The charger shell prepared by the present invention has good processing performance, excellent comprehensive performance and broad market prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of chargers, and in particular relates to a charger shell molding process. Background Art

[0002] Polyphenylene ether is a high-strength engineering plastic developed in the 1960s. Its chemical name is poly-2,6-dimethyl-1,4-phenylene ether, referred to as PPO (Polyphenylene Oxide) or PPE (Polypheylene ether), also known as polyphenylene oxide or polyphenylene ether. PPO resin has a very high glass transition temperature and can maintain good physical and mechanical properties over a wide temperature range, which is crucial for car chargers that are used outdoors and need to withstand extreme temperature changes; as a charging device, good electrical insulation performance is a basic requirement. PPO resin can effectively prevent electrical breakdown and leakage to ensure user safety. At the same time, PPO is a self-extinguishing material that can meet the fire safety requirements of electronic products. Therefore, the car charger housing on the car usually uses polyphenylene ether (PPO) resin as the material.

[0003] With the rapid development of the electric vehicle industry, higher requirements have been placed on the charger shell. However, PPO resin has some shortcomings as a material for on-board chargers in automobiles, which affects its applicability as a charger resin material: (1) Poor processing fluidity: The melt viscosity of polyphenylene ether resin is high, which leads to poor fluidity during processing, such as injection molding or extrusion. Higher processing temperatures and pressures may be required, which not only increases manufacturing costs, but may also affect the dimensional accuracy and surface quality of the product. (2) Tendency to stress cracking: Polyphenylene ether is prone to stress cracking, especially when subjected to mechanical stress or in certain chemical environments, which may affect the long-term reliability and durability of the charger shell. (3) Average impact resistance: The impact strength of PPO resin is relatively low, which makes the charger shell more susceptible to damage or cracking when accidentally hit, reducing the durability of the product.

[0004] Therefore, there is an urgent need for a car charger housing with high fluidity, excellent processing performance and excellent comprehensive performance, which meets the needs of market development and has broad application prospects. Summary of the invention

[0005] The purpose of the present invention is to provide a charger shell molding process, so that the charger shell produced has good processing performance and excellent comprehensive performance.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] A charger shell molding process comprises the following steps:

[0008] (1) Weigh the following raw materials in parts by mass: 50-60 parts of polyphenylene ether resin, 14-19 parts of polycarbonate, 10-17 parts of ASA resin, 1.5-2.5 parts of silane coupling agent, 4-6 parts of modified filler, 0.5-1 parts of lubricant, 0.3-0.8 parts of antioxidant, 1-3 parts of toughening agent, 1-2 parts of thermal stabilizer and 0.3-0.7 parts of anti-dripping agent;

[0009] (2) Mixing polyphenylene ether resin, polycarbonate and ASA resin, heating to 130-140° C., stirring evenly, and continuing to heat to 160-180° C., adding modified filler and silane coupling agent, stirring evenly, and obtaining a premix;

[0010] (3) After adding the remaining components to the premix, the mixture is put into an internal mixer for blending, stirred at 230-240° C. for 40-50 min at a stirring speed of 1000-1200 rpm to obtain a final mixture;

[0011] (4) melt blending the final mixture through a twin-screw extruder, extruding and granulating, the temperature of the first zone of the twin-screw extruder is 230-250° C., the temperature of the second zone is 240-260° C., the temperature of the third zone is 270-280° C., the temperature of the fourth zone is 260-280° C., the head is 270-280° C., the residence time is 2-3 min, and the pressure is 12-18 MPa to obtain pellets;

[0012] (5) The pellets are hot-melt extruded at 270-280° C. and a pressure of 15-20 MPa to obtain a charger shell.

[0013] Polyphenylene ether resin, melt volume flow rate 7.0 cm 3 / 10min, test conditions: 280℃ / 5.0kg. American Basic Innovation N300X NORYL TM Resin.

[0014] Polycarbonate, melt volume flow rate 21.0 cm 3 / 10min, test conditions: 280℃ / 5.0kg. Teijin Brand: MN-3600HA.

[0015] ASA resin melt volume flow rate 7cm 3 / 10min, test conditions: 220℃ / 10kg. Chi Mei ASA ASA, PW-997.

[0016] Polyphenylene ether (PPO) resin is used as the material of the car charger shell. Due to its high melt viscosity and poor melt fluidity, the material is not easy to fill the complex geometric shape of the mold during the injection molding process, which may lead to a decrease in the yield rate and an increase in the scrap rate. At the same time, the poor fluidity makes the material more likely to shrink unevenly during cooling and solidification, resulting in poor dimensional stability of the final product and difficult to control dimensional accuracy. In addition, the charger shell made of polyphenylene ether (PPO) resin has unsatisfactory tensile strength and bending strength, resulting in product durability and reliability that cannot meet consumers' increasing demand for product quality. The present invention improves the fluidity of the charger shell material by compounding polyphenylene ether resin, polycarbonate and ASA resin, improves the processing performance, and improves the tensile strength and bending strength of the charger shell material. The analysis is that by adding polycarbonate and ASA resin, a microscopic homogeneous or microphase separation structure is formed through the complementary properties, thereby improving the fluidity of the polyphenylene ether resin. However, the inventor found that after adding polycarbonate and ASA resin, the impact performance is not ideal.

[0017] Furthermore, the preparation method of the silane coupling agent is:

[0018] Step 1: Mix 4-7 moles of tert-amyl alcohol peroxide with 1 mole of sodium hydroxide, stir and react at 1-3° C. for 150-180 min under a nitrogen atmosphere, filter to obtain a solid, wash and dry to obtain sodium tert-amyl peroxide;

[0019] Step 2: Mix 6-8 mol of sodium peroxide, 1 mol of 3-chloropropylmethyldimethoxysilane and 25-28 mol of toluene, and react at 6-8° C. for 10-13 hours under a nitrogen atmosphere to obtain a reaction product;

[0020] Step 3: Mix the reaction product with a volume ratio of 1:1-2 and a 15wt% sodium hydroxide aqueous solution, let stand for 7-8h, separate the layers, add methanol with a volume of 1.5-2.5 times that of the toluene in step 2 to the organic phase, and remove toluene and methanol by rotary evaporation at 38°C and 25kPa to obtain a silane coupling agent.

[0021] The present invention attempts to add a commercially available silane coupling agent to the system of the present invention to improve the interfacial bonding between the inorganic filler and the resin matrix, thereby improving the impact resistance of the material. However, the inventors found that adding a commercially available silane coupling agent to the system of the present invention did not produce an ideal effect. The analysis showed that the resin system of the present invention had poor reactivity and compatibility with the silane coupling agent, resulting in the silane coupling agent not being able to exert its due effect. The present invention improves the impact resistance of the charger shell material by adding a silane coupling agent. The analysis showed that the silane coupling agent of the present invention has both a methoxy group and a peroxide group. The methoxy group can be rapidly hydrolyzed to generate a highly active silanol group, which can react with groups such as hydroxyl groups on the surface of the modified filler. The peroxide group can directly participate in the reaction of the resin system, which can enhance interfacial bonding, optimize interfacial interactions, form a strong chemical bond bridging effect, and thus improve impact resistance. It was also found that adding a silane coupling agent can improve the thermal deformation temperature of the charger shell.

[0022] Tert-amyl alcohol peroxide, CAS: 3425-61-4. 3-Chloropropylmethyldimethoxysilane, CAS: 18171-19-2.

[0023] Furthermore, the preparation method of the modified filler is:

[0024] S1: mixing hollow ceramic microspheres, carbon nanotubes and mica powder in a mass ratio of 1:1.5-1.9:0.2-0.7 to obtain a mixed filler;

[0025] S2: Disperse the mixed filler in a 45-50wt% ethanol aqueous solution, add silane coupling agent KH560 and a surfactant, react at 55-65°C for 2-3h, centrifuge and dry to obtain a modified filler.

[0026] Furthermore, the silane coupling agent accounts for 2-3% of the mass of the mixed filler.

[0027] Furthermore, the surfactant accounts for 0.4-0.9% of the mass of the mixed filler.

[0028] Furthermore, the surfactant is sodium dodecylbenzene sulfonate.

[0029] Furthermore, the particle size of the hollow ceramic microspheres is 1-10 μm. Shanghai Gerunya Nanomaterials Co., Ltd.

[0030] Furthermore, the mica powder is mica powder with a D90 particle size of 6 μm. Shijiazhuang Chenxing Industrial Co., Ltd.

[0031] Furthermore, the carbon nanotubes have a diameter of 2-4 nm, a length of 40-60 μm, and a specific surface area of ​​400-600 m 2 / g. Xianfeng Nano.

[0032] The present invention mixes and modifies hollow ceramic microbeads, carbon nanotubes and mica powder, and has better binding properties with the self-made silane coupling agent of the present invention, and has stronger dispersibility in the system, and can give full play to the role of hollow ceramic microbeads, carbon nanotubes and mica powder, thereby improving the friction of the charger housing. Analysis shows that by compounding hollow ceramic microbeads, carbon nanotubes and mica powder with different physicochemical parameters, the overall density of the material can be improved, the matrix strength can be enhanced, the stress distribution can be improved, the wear contact surface can be reduced, and the wear can be reduced. When hollow ceramic microbeads, carbon nanotubes and mica powder are compounded in a specific ratio, the water absorption of the charger housing is improved at the same time.

[0033] Furthermore, the lubricant is selected from one or more of calcium stearate, paraffin, and zinc stearate.

[0034] Furthermore, the toughening agent is oxidized polyethylene wax, which is purchased from Qihong Polymer Materials Co., Ltd., model: high-density oxidized polyethylene wax S-3815.

[0035] Furthermore, the thermal stabilizer is methyl methacrylate.

[0036] Furthermore, the antioxidant is antioxidant 1076.

[0037] Furthermore, the anti-drip agent is anti-drip agent 3300.

[0038] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0039] 1. The present invention improves the fluidity of the charger shell material and the processing performance by compounding polyphenylene ether resin, polycarbonate and ASA resin, and at the same time improves the tensile strength and bending strength of the charger shell material.

[0040] 2. The present invention improves the impact resistance of the charger shell material by adding a silane coupling agent; it is also found that adding a silane coupling agent can improve the thermal deformation temperature of the charger shell.

[0041] 3. The present invention mixes and modifies hollow ceramic microbeads, carbon nanotubes and mica powder, which have better binding properties with the homemade silane coupling agent of the present invention, stronger dispersibility in the system, and improves the friction of the charger housing; at the same time, it improves the water absorption of the charger housing.

[0042] In summary, the material fluidity of the charger shell provided by the present invention is high, and various details of the mold can be filled faster and more fully during the injection molding process, shortening the molding cycle, improving production efficiency, and reducing energy consumption and costs. High-fluidity materials can more easily flow to the far end or narrow area of ​​the mold, ensuring the integrity of the molded product, reducing defects such as lack of material, shrinkage or bubbles, and thus improving product quality. Good fluidity helps to obtain a smoother and more uniform surface effect, reduce surface defects caused by uneven filling, and achieve high-quality appearance requirements without too much subsequent processing. At the same time, it can improve the flexibility of the charger's appearance design, which is conducive to innovative design and the development of differentiated products.

[0043] The charger shell provided by the present invention has excellent comprehensive performance and meets high standards in multiple key indicators, which is crucial for user safety, user experience, environmental adaptability and long-term reliability. The charger shell of the present invention has good insulation and flame retardancy, which can effectively prevent the risk of electric shock and fire, and ensure the safety of users during use. The shell material is wear-resistant and impact-resistant, and is not easy to crack or deform. Even if it accidentally falls or collides during daily use, it can maintain structural integrity and extend its service life. It also has good waterproof performance and can resist the intrusion of moisture in daily life, making it suitable for more usage scenarios. DETAILED DESCRIPTION

[0044] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0045] Example 1

[0046] This embodiment provides a charger shell molding process, including the following steps:

[0047] (1) Weigh the following raw materials in parts by weight: 55 parts of polyphenylene ether resin, 17 parts of polycarbonate, 15 parts of ASA resin, 2.1 parts of silane coupling agent, 5 parts of modified filler, 0.7 parts of lubricant, 0.6 parts of antioxidant, 2 parts of toughening agent, 1.4 parts of thermal stabilizer and 0.4 parts of anti-dripping agent;

[0048] (2) Mixing polyphenylene ether resin, polycarbonate and ASA resin, heating to 135° C., stirring evenly, and continuing to heat to 170° C., adding modified filler and silane coupling agent, stirring evenly, and obtaining a premix;

[0049] (3) After adding the remaining components to the premix, the mixture was put into an internal mixer for blending, and stirred at 235° C. for 45 min at a stirring speed of 1100 rpm to obtain a final mixture;

[0050] (4) The final mixture was melt-blended and extruded into pellets through a twin-screw extruder. The temperature of the first zone of the twin-screw extruder was 240° C., the temperature of the second zone was 250° C., the temperature of the third zone was 275° C., the temperature of the fourth zone was 270° C., the die head was 275° C., the residence time was 3 min, and the pressure was 15 MPa to obtain pellets.

[0051] (5) The pellets are hot-melt extruded at 275° C. and a pressure of 17 MPa to obtain a charger shell.

[0052] Polyphenylene ether resin, melt volume flow rate 7.0 cm 3 / 10min, test conditions: 280℃ / 5.0kg. American Basic Innovation N300X NORYL TM Resin.

[0053] Polycarbonate, melt volume flow rate 21.0 cm 3 / 10min, test conditions: 280℃ / 5.0kg. Japanese emperor Brand: MN-3600HA.

[0054] ASA resin melt volume flow rate 7cm 3 / 10min, test conditions: 220℃ / 10kg. Chi Mei ASA ASA, PW-997.

[0055] The preparation method of the silane coupling agent is:

[0056] Step 1: Mix 6 mol of tert-amyl alcohol peroxide and 1 mol of sodium hydroxide, stir and react at 2° C. for 160 min under a nitrogen atmosphere, filter to obtain a solid, wash and dry to obtain sodium tert-amyl peroxide;

[0057] Step 2: 7 mol of sodium peroxide, 1 mol of 3-chloropropylmethyldimethoxysilane and 27 mol of toluene were mixed, and reacted at 7° C. for 12 h under a nitrogen atmosphere to obtain a reaction product;

[0058] Step 3: Mix the reaction product with a volume ratio of 1:1.4 and 15 wt% sodium hydroxide aqueous solution, let stand for 7.5 hours, separate the layers, add methanol twice the volume of the toluene in step 2 to the organic phase, and remove toluene and methanol by rotary evaporation at 38°C and 25 kPa to obtain a silane coupling agent.

[0059] Tert-amyl alcohol peroxide, CAS: 3425-61-4. 3-Chloropropylmethyldimethoxysilane, CAS: 18171-19-2.

[0060] The preparation method of the modified filler is:

[0061] S1: mixing hollow ceramic microspheres, carbon nanotubes and mica powder in a mass ratio of 1:1.6:0.5 to obtain a mixed filler;

[0062] S2: The mixed filler is dispersed in a 47 wt % ethanol aqueous solution, and a silane coupling agent KH560 and a surfactant are added, reacted at 60° C. for 2.5 h, centrifuged and dried to obtain a modified filler.

[0063] The silane coupling agent accounts for 2.6% of the mass of the mixed filler.

[0064] The surfactant accounts for 0.7% of the mixed filler mass.

[0065] The surfactant is sodium dodecylbenzene sulfonate.

[0066] The particle size of hollow ceramic microspheres is 1-10 μm. Shanghai Gerunya Nanomaterials Co., Ltd.

[0067] The mica powder is mica powder with a D90 particle size of 6 μm. Shijiazhuang Chenxing Industrial Co., Ltd.

[0068] The carbon nanotubes have a diameter of 2-4 nm, a length of 40-60 μm, and a specific surface area of ​​400-600 m 2 / g. Xianfeng Nano.

[0069] The lubricant is calcium stearate.

[0070] The toughening agent is oxidized polyethylene wax, which was purchased from Qihong Polymer Materials Co., Ltd., model: high-density oxidized polyethylene wax S-3815.

[0071] The heat stabilizer is methyl methacrylate.

[0072] The antioxidant is antioxidant 1076.

[0073] The anti-drip agent is anti-drip agent 3300.

[0074] Example 2

[0075] This embodiment provides a charger shell molding process, including the following steps:

[0076] (1) Weigh the following raw materials in parts by mass: 50 parts of polyphenylene ether resin, 19 parts of polycarbonate, 10 parts of ASA resin, 1.5 parts of silane coupling agent, 6 parts of modified filler, 1 part of lubricant, 0.3 parts of antioxidant, 3 parts of toughening agent, 1 part of thermal stabilizer and 0.7 parts of anti-dripping agent;

[0077] (2) polyphenylene ether resin, polycarbonate and ASA resin are mixed, heated to 140° C., stirred evenly, and then heated to 180° C., modified filler and silane coupling agent are added, stirred evenly, and a premix is ​​obtained;

[0078] (3) After adding the remaining components to the premix, the mixture was put into an internal mixer for blending, and stirred at 240° C. for 50 min at a stirring speed of 1200 rpm to obtain a final mixture;

[0079] (4) The final mixture was melt-blended and extruded into pellets through a twin-screw extruder. The temperature of the first zone of the twin-screw extruder was 250° C., the temperature of the second zone was 240° C., the temperature of the third zone was 280° C., the temperature of the fourth zone was 260° C., the die head was 280° C., the residence time was 2 min, and the pressure was 18 MPa to obtain pellets;

[0080] (5) The pellets are hot-melt extruded at 270° C. and a pressure of 20 MPa to obtain a charger shell.

[0081] Polyphenylene ether resin, melt volume flow rate 7.0 cm 3 / 10min, test conditions: 280℃ / 5.0kg. American Basic Innovation N300X NORYL TM Resin.

[0082] Polycarbonate, melt volume flow rate 21.0 cm 3 / 10min, test conditions: 280℃ / 5.0kg. Japanese emperor Brand: MN-3600HA.

[0083] ASA resin melt volume flow rate 7cm 3 / 10min, test conditions: 220℃ / 10kg. Chi Mei ASA ASA, PW-997.

[0084] The preparation method of the silane coupling agent is:

[0085] Step 1: Mix 4 mol of tert-amyl alcohol peroxide with 1 mol of sodium hydroxide, stir and react at 1° C. for 150 min under a nitrogen atmosphere, filter to obtain a solid, wash and dry to obtain sodium tert-amyl peroxide;

[0086] Step 2: 6 mol of sodium peroxide, 1 mol of 3-chloropropylmethyldimethoxysilane and 25 mol of toluene were mixed, and reacted at 6° C. for 10 h under a nitrogen atmosphere to obtain a reaction product;

[0087] Step 3: Mix the reaction product in a volume ratio of 1:1 with a 15 wt% sodium hydroxide aqueous solution, let stand for 7 hours, separate the layers, add methanol in an amount 1.5 times the volume of the toluene in step 2 to the organic phase, and remove toluene and methanol by rotary evaporation at 38°C and 25 kPa to obtain a silane coupling agent.

[0088] Tert-amyl alcohol peroxide, CAS: 3425-61-4. 3-Chloropropylmethyldimethoxysilane, CAS: 18171-19-2.

[0089] The preparation method of the modified filler is:

[0090] S1: mixing hollow ceramic microspheres, carbon nanotubes and mica powder in a mass ratio of 1:1.9:0.2 to obtain a mixed filler;

[0091] S2: Disperse the mixed filler in a 45 wt % ethanol aqueous solution, add silane coupling agent KH560 and a surfactant, react at 65° C. for 3 h, centrifuge and dry to obtain a modified filler.

[0092] The silane coupling agent accounts for 3% of the mass of the mixed filler.

[0093] The surfactant accounts for 0.9% of the mixed filler mass.

[0094] The surfactant is sodium dodecylbenzene sulfonate.

[0095] The particle size of hollow ceramic microspheres is 1-10 μm. Shanghai Gerunya Nanomaterials Co., Ltd.

[0096] The mica powder is mica powder with a D90 particle size of 6 μm. Shijiazhuang Chenxing Industrial Co., Ltd.

[0097] The carbon nanotubes have a diameter of 2-4 nm, a length of 40-60 μm, and a specific surface area of ​​400-600 m 2 / g. Xianfeng Nano.

[0098] The lubricant is zinc stearate.

[0099] The toughening agent is oxidized polyethylene wax, which was purchased from Qihong Polymer Materials Co., Ltd., model: high-density oxidized polyethylene wax S-3815.

[0100] The heat stabilizer is methyl methacrylate.

[0101] The antioxidant is antioxidant 1076.

[0102] The anti-drip agent is anti-drip agent 3300.

[0103] Comparative Example 1

[0104] The difference between this comparative example and Example 1 is: weigh the following raw materials in parts by mass: 69 parts of polyphenylene ether resin, 10 parts of polycarbonate, 8 parts of ASA resin, 2.1 parts of silane coupling agent, 5 parts of modified filler, 0.7 parts of lubricant, 0.6 parts of antioxidant, 2 parts of toughening agent, 1.4 parts of heat stabilizer and 0.4 parts of anti-dripping agent.

[0105] Comparative Example 2

[0106] The difference between this comparative example and Example 1 is that the silane coupling agent in step (1) is a commercially available product, γ-aminopropyltriethoxysilane, CAS: 919-30-2.

[0107] Comparative Example 3

[0108] The difference between this comparative example and Example 1 is that the preparation method of the modified filler is:

[0109] S1: mixing hollow ceramic microspheres, carbon nanotubes and mica powder in a mass ratio of 1:1:1 to obtain a mixed filler;

[0110] S2: The mixed filler is dispersed in a 47 wt % ethanol aqueous solution, and a silane coupling agent KH560 and a surfactant are added, reacted at 60° C. for 2.5 h, centrifuged and dried to obtain a modified filler.

[0111] Comparative Example 4

[0112] The difference between this comparative example and Example 1 is that the preparation method of the modified filler is:

[0113] S1: mixing silicon dioxide, calcium carbonate and titanium dioxide in a mass ratio of 1:1.6:0.5 to obtain a mixed filler;

[0114] S2: The mixed filler is dispersed in a 47 wt % ethanol aqueous solution, and a silane coupling agent KH560 and a surfactant are added, reacted at 60° C. for 2.5 h, centrifuged and dried to obtain a modified filler.

[0115] The average particle size of silicon dioxide is 50nm and the average specific surface area is 210m 2 / g. Ningbo Jinlei Nanomaterial Technology Co., Ltd.

[0116] Calcium carbonate, 800 mesh, Hebei Huishun Mining Co., Ltd.

[0117] Titanium dioxide, particle size 3-5nm, Ningbo Jiwei Nano New Material Technology Co., Ltd.

[0118] Comparative Example 5

[0119] The difference between this comparative example and Example 1 is:

[0120] Hollow ceramic microspheres with particle size of 20-500μm. Dalian Yibang Technology Co., Ltd., model: E-SPHERES hollow ceramic microspheres.

[0121] The mica powder is mica powder with a D90 particle size of 20 μm. Shijiazhuang Chenxing Industrial Co., Ltd.

[0122] Carbon nanotubes, 5-15nm, length: 80-150μm, specific surface area 200-300m 2 / g. Xianfeng Nano.

[0123] Comparative Example 6

[0124] The difference between this comparative example and Example 1 is that the resin parameters are different.

[0125] Polyphenylene ether resin, melt volume flow rate 3.5 cm 3 / 10min, test conditions: 280℃ / 5.0kg. NORYL TM PPO VO150B.

[0126] Polycarbonate, melt volume flow 7cm 3 / 10min, test conditions: 280℃ / 5.0kg. Japanese emperor Brand: AM-1300.

[0127] ASA resin melt volume flow rate 4cm 3 / 10min, test conditions: 220℃ / 10kg. ASA, PW-997S.

[0128] Performance Testing

[0129] The performance test of the pellets prepared in Examples 1-2 and Comparative Examples 1-6 was performed

[0130] 1. Tensile strength: refer to standard ASTMD638 to measure tensile strength;

[0131] 2. Bending strength: refer to standard ASTMD790 to measure the bending strength;

[0132] 3. Impact strength: refer to standard ASTMD256 to measure the impact strength;

[0133] 4. Heat deformation temperature: Determine the heat deformation temperature according to ASTM D-648;

[0134] 5. Flame retardant grade: refer to standard UL94 (1.6mm) to determine the flame retardant grade;

[0135] 6. Water absorption: refer to standard IPC-TM-60 to determine water absorption;

[0136] 7. Friction coefficient: The friction coefficient is determined according to standard ASTM D3702.

[0137] 8. Flowability: Use Archimedean spiral cavity plate for injection molding test. The injection molding wall thickness is 2mm, the width is 5mm, the injection molding temperature is 280℃, the injection molding pressure is 100MPa, the cooling time is 10s, the holding pressure is 70MPa, the holding time is 10s, and the spiral flow length is measured.

[0138] Table 1 Performance test results

[0139]

[0140] The results show that the comprehensive performance of the charger shell materials prepared in Examples 1-2 of the present invention is excellent. Comparative Examples 1-6 show that the comprehensive performance decreases to varying degrees when the raw materials and conditions of preparation are changed.

[0141] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A charger shell molding process, characterized in that: The following steps are involved: (1) Weigh the following raw materials in parts by mass: 50-60 parts of polyphenylene ether resin, 14-19 parts of polycarbonate, 10-17 parts of ASA resin, 1.5-2.5 parts of silane coupling agent, 4-6 parts of modified filler, 0.5-1 parts of lubricant, 0.3-0.8 parts of antioxidant, 1-3 parts of toughening agent, 1-2 parts of heat stabilizer and 0.3-0.7 parts of anti-dripping agent; (2) Mix polyphenylene ether resin, polycarbonate and ASA resin, heat to 130-140°C, stir evenly, continue to heat to 160-180°C, add modified filler and silane coupling agent, stir evenly to obtain a premix; (3) After adding the remaining components to the premix, the mixture is put into an internal mixer for blending, stirred at 230-240° C. for 40-50 min at a stirring speed of 1000-1200 rpm to obtain a final mixture; (4) The final mixture is melt-blended and extruded into granules through a twin-screw extruder, the temperature of the first zone of the twin-screw extruder is 230-250°C, the temperature of the second zone is 240-260°C, the temperature of the third zone is 270-280°C, the temperature of the fourth zone is 260-280°C, the head is 270-280°C, the residence time is 2-3 min, and the pressure is 12-18 MPa to obtain granules; (5) hot-melt extrusion molding the pellets at 270-280° C. and 15-20 MPa to obtain a charger shell; The preparation method of the silane coupling agent is: Step 1: Mix 4-7 moles of tert-amyl alcohol peroxide with 1 mole of sodium hydroxide, stir and react at 1-3° C. for 150-180 min under a nitrogen atmosphere, filter to obtain a solid, wash and dry to obtain sodium tert-amyl peroxide; Step 2: Mix 6-8 mol of sodium peroxide, 1 mol of 3-chloropropylmethyldimethoxysilane and 25-28 mol of toluene, and react at 6-8° C. for 10-13 hours under a nitrogen atmosphere to obtain a reaction product; Step 3: Mix the reaction product with a volume ratio of 1:1-2 and a 15wt% sodium hydroxide aqueous solution, let stand for 7-8h, separate the layers, add methanol with a volume of 1.5-2.5 times that of the toluene in step 2 to the organic phase, and remove toluene and methanol by rotary evaporation at 38°C and 25kPa to obtain a silane coupling agent; The preparation method of the modified filler is: S1: mixing hollow ceramic microspheres, carbon nanotubes and mica powder in a mass ratio of 1:1.5-1.9:0.2-0.7 to obtain a mixed filler; S2: Disperse the mixed filler in a 45-50wt% ethanol aqueous solution, add silane coupling agent KH560 and sodium dodecylbenzene sulfonate, react at 55-65°C for 2-3h, centrifuge and dry to obtain a modified filler; The silane coupling agent KH560 accounts for 2-3% of the mixed filler mass; The sodium dodecylbenzene sulfonate accounts for 0.4-0.9% of the mass of the mixed filler; The particle size of the hollow ceramic microspheres is 1-10 μm; The mica powder is mica powder with a D90 particle size of 6 μm; The carbon nanotubes have a diameter of 2-4 nm, a length of 40-60 μm, and a specific surface area of ​​400-600 m 2 / g; The melt volume flow rate of polyphenylene ether resin is 7.0 cm³ / 10min, and the test conditions are 280℃ / 5.0 kg. Polycarbonate melt volume flow rate 21.0cm³ / 10min, test conditions: 280℃ / 5.0kg; ASA resin melt volume flow rate 7 cm³ / 10 min, test conditions: 220℃ / 10 kg.

2. The charger shell molding process according to claim 1, characterized in that: The lubricant is selected from one or more of calcium stearate, paraffin and zinc stearate.

3. The charger shell molding process according to claim 1, characterized in that: The toughening agent is oxidized polyethylene wax.

Citation Information

Patent Citations

  • Power distribution box case material and preparation method thereof

    CN108976751A

  • Wear-resistant PC / ASA alloy material and preparation method thereof

    CN109385063A